Determinasi Continuance Intention dalam Penggunaan M-Payment - Desi Novita Sari (Universitas Muhammadiyah Purwokerto, 2024)
This study aims to analyze the impact of Information Quality, System Quality, and Service Quality on Continuance Intention in m-payment service usage, with Satisfaction as a mediating variable. M-payment has become one of the key innovations in the digital financial ecosystem, offering convenience, flexibility, and efficiency in transactions. The research data was collected through an online survey of 62 experienced m-payment service users. The results of the analysis indicate that the Information Quality variable has a significant positive effect on Continuance Intention through the mediation of Satisfaction, while System Quality and Service Quality do not show a significant impact on Continuance Intention, either directly or through Satisfaction. These findings highlight the importance of information quality in building user satisfaction, which in turn enhances the continued intention to use m-payment services. In contrast, system and service quality may require a broader strategic approach to maximize user loyalty. This research provides both theoretical and practical contributions in developing digital service strategies that focus on user experience